2009
DOI: 10.5858/133.9.1448
|View full text |Cite
|
Sign up to set email alerts
|

Primary Leiomyosarcoma of Extragnathic Bone: Clinicopathologic Features and Reevaluation of Prognosis

Abstract: Context.—Leiomyosarcoma most commonly involves the female genital tract and occasionally arises within the retroperitoneum, abdominal cavity, or the soft tissues of the extremity. Presentation as a primary bone tumor is extraordinarily uncommon, potentially leading to misdiagnosis. The prognosis is traditionally thought to be dismal. However, this conclusion is largely based on individual case reports and small series, in some of which the pathologic diagnosis is not well documented. Objective.—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 47 publications
1
12
0
1
Order By: Relevance
“…Adelani et al reviewed 107 skeletal leiomyosarcomas that had been previously reported in the English literature. 3 Age of presentation varied from 9- to 87-years with a median age of 47 years, which is younger than its soft tissue counterpart. 4 Males and females were almost equally affected.…”
Section: Discussionmentioning
confidence: 99%
“…Adelani et al reviewed 107 skeletal leiomyosarcomas that had been previously reported in the English literature. 3 Age of presentation varied from 9- to 87-years with a median age of 47 years, which is younger than its soft tissue counterpart. 4 Males and females were almost equally affected.…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemistry is required for an accurate diagnosis, especially when the tumor is poorly differentiated or undifferentiated [ 12 , 17 ]. Differential diagnosis is made with the following tumors [ 1 , 7 , 8 , 10 , 12 , 17 ]: (i) undifferentiated pleomorphic sarcoma: epithelioid or spindle tumoral cells, with high-grade and bizarre cytology, frequent mitotic figures and areas of necrosis; it can associate stroma with myxoid changes, areas of inflammation and giant cells, but despite all these aspects, it can still present with an ambiguous morphology and IHC profile; (ii) myofibroblastic sarcoma: tumoral cells have amphophilic cytoplasm, short and tapered nuclei, IHC staining for muscle markers is patchy not diffuse; (iii) fibrosarcoma: presence of elongated-ended fusiform nuclei not with blunted edges; (iv) osteosarcoma: focal osteoid formation and lack of myogenic markers; (v) chondrosarcoma: chondroid formation; (vi) malignant fibrous histiocytoma: evident storiform pattern and bland nuclei; (vii) metastatic sarcomatoid carcinoma: negative muscle markers in immunohistochemistry; (viii) leiomyoma of bone: no mitotic activity and no cytological atypia is present. The TNM–G classification of STS according to American Joint Committee on Cancer (AJCC) take into consideration the dimension of the tumor (T), presence of regional lymph node (N) metastasis, distant metastasis (M) and histological tumor grade (G) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the immunophenotype, the cells present with smooth muscle differentiation: positive, diffuse staining with desmin, h-caldesmon, SMA [1]. The immunohistochemistry is required for an accurate diagnosis, especially when the tumor is poorly differentiated or undifferentiated [12,17].…”
Section:  Discussionmentioning
confidence: 99%
“…16 En los últimos años, las técnicas de diagnóstico por inmunohistoquímica han mejorado, por lo que esta tasa podría aumentar. 3,12 Según la revisión de Adelani et al, 17 publicada en 2009 con base en 107 casos reportados en la literatura en inglés, se presenta con mayor frecuencia en hombres adultos de 40 años (rango: 9-87 años); en este reporte, el caso corresponde a una paciente de sexo femenino, en edad joven.…”
Section: Discussionunclassified